Treating Depression in Older Adults: Challenges to Implementing the Recommendations of an Expert Panel - Mark Snowden, MD, MPH; Lesley Steinman, MSW, MPH; John Frederick, MD (Preventing Chronic Disease, 2008)
Depression is increasingly recognized as a significant public health problem among older adults. Because the condition is highly treatable and currently undertreated among community-based older adults, late-life depression is an appropriate focus for disease prevention programs. We report findings from a recent project to review the scientific literature for published reports about treatment for depression among community-dwelling older adults and to recommend the interventions with proven effectiveness. We also summarize the research findings related to each recommended intervention and describe the elements of each. To show the difficulties involved in translating research into practice, we describe real-world experiences in implementing these evidence-based interventions in various community settings. Because depression among older people is viewed more and more as a public health problem, we suggest that partnerships of providers, patients, and policy makers be forged to overcome challenges related to funding, training, and implementing treatments for this condition.